2017
DOI: 10.3390/molecules22122244
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Synthetic and Industrial Effluents by Aspergillus niger Isolated from Contaminated Soil Following a Sequential Strategy

Abstract: The present study aimed to assess and compare the ability to remediate synthetic textile and industrial wastewaters by Fenton treatment, a biological system and sequential treatments using Aspergillus niger (A. niger). All studied treatments were found to be effective in decolorization of the effluents under study. Fenton treatment followed by A. niger showed excellent potential for the maximum decolorization of the synthetic and industrial effluents under study. The effectiveness of sequential treatment was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…The role of laccases in the degradation of lignin in nature has been extensively reported (Fonseca et al 2010). These lignin-degrading enzymes are directly involved not only in the degradation of lignin in their natural lignocellulosic substrates but also in the degradation of various xenobiotic compounds, including dye (Gulzar et al 2017) and recalcitrant compounds found in effluents, helping thus the tolerance and survival of fungus in hostile environments. In this sense, P. sajor-caju could be ranked as promising polychlorinated biphenyls degraders of chlorinated organic pollutants (Sadañoski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The role of laccases in the degradation of lignin in nature has been extensively reported (Fonseca et al 2010). These lignin-degrading enzymes are directly involved not only in the degradation of lignin in their natural lignocellulosic substrates but also in the degradation of various xenobiotic compounds, including dye (Gulzar et al 2017) and recalcitrant compounds found in effluents, helping thus the tolerance and survival of fungus in hostile environments. In this sense, P. sajor-caju could be ranked as promising polychlorinated biphenyls degraders of chlorinated organic pollutants (Sadañoski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have suggested different processes and technologies for the remediation of textile wastewater [40][41][42][43]; most of them have employed microbial agents, including bacterial and fungal species, from a variety of sources [44]. Agricultural residual materials have complex structures with high strength, environmentally friendly nature, low cost, and global availability.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Initial dye concentrations usually range from 50-1000 mg/L. Decolorizations mainly depend on the nature of the microbe and type of dye in use [20].…”
Section: Effect Of Synthetic Dye Wastewater Concentrationmentioning
confidence: 99%